Aplicação do QRCODE para destinação de lixo hospitalar - Santana, Gerge Mazul (2016)
This paper aims to present a methodology to implement a process model for allocation of medical waste, from its receiving to its disposal, using technology QRCODE (Quick Response), or quick response code. To create this model has developed its own methodology using free software tools such as Java, MySQL, Web Service and highlighted the Android, because the model is applied for Smartphones and Tablets with Android operating system. Model provision a better control of hospital material, resulting in a better quality of the process and the correct disposal of this material, which by law must be designed properly, thus avoiding risk of contamination or other problem.